Social Media Management in Enhancing Educational Institutions' Reputation (A Multi-Case Study at SMK Muhammadiyah Lumajang and MAN Lumajang) - Sawiji, Bekti; Maimun, Agus; Susilawati, Samsul (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research aims to analyze and discover the design, implementation, and results of social media in building the reputation of educational institutions. The approach used in this study is qualitative with a case study method using a multicase design. The study focuses on two case studies: SMK Muhammadiyah Lumajang and MAN Lumajang, both of which are renowned educational institutions in Indonesia with a commitment to optimizing social media. Data collection techniques employed include in-depth interviews, documentation, and observation. The data analysis method used is constant comparison. The technique for ensuring data validity include credibility, transferability, dependability, and confirmability. The results of this research are as follows: First, the design of social media to enhance the reputation of educational institutions consists of four managerial processes: (1) Identification of Core Resources and Supporting Resources, (2) Formulation of Goals and Objectives, (3) Selection of Social Media Platforms, and (4) Task Force Team. Second, the implementation of social media design includes activities such as: (1) Content Formulation, (2) Broadcast and Q&A, (3) Collaboration with Internal and External Human Resources of the Institution, (4) Control through System Control, Leadership Control, and Social Control approaches, and (5) Development of Platform Types, Expanding Audience Segments, Updating Strategies, and Revitalizing Social Media Orientation. Third, the outcomes and impact of social media include: Quantitative results manifested as an increase in new student admissions, and qualitative impact in the form of a New Work Culture and Institutional Engagement.